Measuring the CMB spectral distortions with COSMO: the multi-mode antenna system - Manzan, Elenia; Albano, Lorenzo; Franceschet, Cristian; Battistelli, Elia S.; De Bernardis, Paolo; Bersanelli, Marco; Cacciotti, Federico; Capponi, Alessandro; Columbro, Fabio; Conenna, Giulia; Coppi, Gabriele; Coppolecchia, Alessandro; et al. (Millimeter, Submillimeter, and Far-Infrared Detectors and Instrumentation for Astronomy XII, 2024)
In this work, we present the design and manufacturing of the two multi-mode antenna arrays of the COSMO experiment and the preliminary beam pattern measurements of their fundamental mode compared with simulations. COSMO is a cryogenic Martin-Puplett Fourier Transform Spectrometer that aims at measuring the isotropic y-type spectral distortion of the Cosmic Microwave Background from Antarctica, by performing differential measurements between the sky and an internal, cryogenic reference blackbody. To reduce the atmospheric contribution, a spinning wedge mirror performs fast sky-dips at varying elevations while fast, low-noise Kinetic Inductance detectors scan the interferogram. Two arrays of antennas couple the radiation to the detectors. Each array consists of nine smooth-walled multi-mode feed-horns, operating in the 120−180 GHz and 210−300 GHz range, respectively. The multi-mode propagation helps increase the instrumental sensitivity without employing large focal planes with hundreds of detectors. The two arrays have a step-linear and a linear profile, respectively, and are obtained by superimposing aluminum plates made with CNC milling. The simulated multi-mode beam pattern has a { 20° − 26° FWHM for the low-frequency array and {16° FWHM for the high-frequency one. The side lobes are below −15 dB. To characterize the antenna response, we measured the beam pattern of the fundamental mode using a Vector Network Analyzer, in far-field conditions inside an anechoic chamber at room temperature. We completed the measurements of the low-frequency array and found a good agreement with the simulations. We also identified a few non-idealities that we attribute to the measuring setup and will further investigate. A comprehensive multi-mode measurement will be feasible at cryogenic temperature once the full receiver is integrated.